2017
DOI: 10.1002/lary.26886
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of powered intracapsular tonsillectomy in children: A meta‐analysis

Abstract: With regard to intraoperative morbidity and postoperative morbidity, PITA is a safe procedure. However, there are high levels of heterogeneity with regard to several measured parameters. Therefore, further large, well-designed trials are required to substantiate our findings. Laryngoscope, 128:732-744, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Third, despite reviewing the processes for the time period spanning the D/K protocol, we were unable to come up with an explanation for why our total anesthesia time was unstable. Fourth, this project may not be generalizable to all T&A techniques—none of the otolaryngologists operating at BSC during this time period utilized the coblation technique, and surgeries performed via microdebrider (tonsillotomy) were not included as there are data showing less pain with this technique . Finally, some surgeons administered local anesthetic but we did not import these data into MDmetrix OR Advisor, so we could not discern whether patients that received local anesthetic had reduced pain scores compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, despite reviewing the processes for the time period spanning the D/K protocol, we were unable to come up with an explanation for why our total anesthesia time was unstable. Fourth, this project may not be generalizable to all T&A techniques—none of the otolaryngologists operating at BSC during this time period utilized the coblation technique, and surgeries performed via microdebrider (tonsillotomy) were not included as there are data showing less pain with this technique . Finally, some surgeons administered local anesthetic but we did not import these data into MDmetrix OR Advisor, so we could not discern whether patients that received local anesthetic had reduced pain scores compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures were performed using electrocautery and/or sharp dissection—seven of 10 otolaryngologists used electrocautery as their primary technique, whereas three utilized sharp dissection. Surgeries performed via microdebrider were excluded as there are data showing less postoperative pain with this technique . Seven of 10 surgeons administered local anesthetic during the procedure according to their preference.…”
Section: Methodsmentioning
confidence: 99%
“…Despite being performed by the minority of otolaryngologists surveyed in our study, IT may be the preferred surgical treatment of SDB and OSA due to evidence showing equivalent efficacy and lower morbidity of IT compared to ET. 4,6 However, respondents to our survey often cited a lack of evidence for supporting IT as their reason for not performing the procedure.…”
Section: Evidence-based Surgical Practicementioning
confidence: 98%
“…3 Since this initial description, the procedure has steadily gained popularity in the United States and across the world as an alternative to traditional extracapsular tonsillectomy (ET). 3 The potential advantages of IT are documented across numerous retrospective and prospective clinical studies 4 as well as randomized controlled trials. 5,6 A recent meta-analysis of randomized controlled trials concluded that, when compared to ET, IT demonstrates a reduced incidence of postoperative hemorrhage, reduced postoperative pain, reduced need for analgesics, more rapid rate of return to normal diet, and fewer days before returning to normal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Powered intracapsular tonsillectomy is associated with lower mortality and morbidity compared to cold steel, coblation, electrodissection, laser, and radio frequency [23] . Lee et al [24] have suggested that powered intracapsular tonsillectomy can significantly decrease postoperative pain, the amount of analgesia, time to resumption of normal diet and activity, and incidence of postoperative admissions (due to dehydration or postoperative bleeding control) compared to the control in their recent meta-analysis. Kim et al [25] have also suggested that intracapsular tonsillectomy can effectively reduce postoperative pain and bleeding which can shorten the time required to return to normal life.…”
Section: Powered Intracapsular Tonsillotomymentioning
confidence: 99%